Determinants of dividend policy in Palestinian banks - Yarob Kullab; Nabil Messabia; Issam Altaweel; Mohammed Shehada (Accounting, 2022)
This study aims to examine whether the dividend theories that were principally developed for non-financial companies in developed institutional environments can explain the dividend policies of banks in Palestine, an emerging market with a high level of uncertainty. It also aims to determine the main factors affecting the banks’ propensity to pay dividends and the banks’ dividend payout ratios. The study uses pooled Probit and ordinary least squares regressions to analyze 10 years of data from all listed banks in the Palestine Stock Exchange Market. The results indicate that agency cost, signaling, and regulatory pressure theories are valid for Palestinian banks. In addition, the analysis shows that bank size, profitability, and capital adequacy are the main positive determinants of Palestinian banks’ propensity to pay dividends and of the dividend payout ratios. Furthermore, after winsorizing the data, the results were found to remain consistent. Finally, the results of a general dominance analysis revealed that bank size is the most important determinant, followed by bank profitability and bank capital adequacy, all three of which positively influence dividend policy decisions in Palestinian banks. This study is among the first to investigate dividend policy determinants in the financial sector. Moreover, this study is conducted in Palestine, an emerging economy. Furthermore, unlike prior studies, this study considers banks’ propensity to pay dividends and banks’ dividend payout ratios concurrently when analyzing the dividend determinants in order to make a significant contribution to solving the dividend determinant puzzle.